(untitled) - Honey, Michael K. (New York, 2018)
Phase one of King’s agenda led to the Civil Rights and Voting Rights acts. But King also questioned what good it does a person to "eat at an integrated lunch counter if he doesn’t earn enough money to buy a hamburger and a cup of coffee?" In phase two of his activism, King organized poor people and demonstrated for union rights while seeking a "moral revolution" to replace the self-seeking individualism of the rich with an overriding concern for the common good. “Either we go up together or we go down together,” King cautioned, a message just as urgent in America today as then. To the Promised Land challenges us to think about what it would mean to truly fulfill King’s legacy and move toward his vision of "the promised land" in our own time.
Keywords: Người Mỹ gốc Phi,African Americans; Điều kiện kinh tế,Economic conditions; 20th century; Thế kỷ 20